Gluttony and Sloth? Calories, Labor Market Activity and the Rise of Obesity. Issue 6 (21st December 2016) - Griffith, Rachel; Lluberas, Rodrigo; Lührmann, Melanie
Abstract: The rise in obesity has largely been attributed to an increase in calorie consumption. We show that official government household survey data indicate that levels of calorie consumption have declined in England between 1980 and 2013; while there has been an increase in calories from food eaten out at restaurants, fast food, soft drinks and confectionery, overall there has been a decrease in total calories purchased. Households have shifted towards more expensive calories, both by substituting away from home production towards market production, and substituting towards higher quality foods. We show that the decline in calories can be partially, but not entirely, rationalized with weight gain by a decline in the strenuousness of work and daily life.